Idiopathic mesenteric phlebosclerosis associated with long-term use of Chinese herbal medicine - Hsing-Jung Yeh,; Pao-Ying Lin,; Wei-Yu Kao,; Ching-Huei Kun,; Chun-Chao Chang, (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Yeh HJ, Lin PY, Kao WY, Kun CH, Chang CC. Idiopathic mesenteric phlebosclerosis associated with long-term use of Chinese herbal medicine. Turk J Gastroenterol 2018; 29: 136-8.